Autophagy and intermittent fasting: the connection for cancer therapy? - Antunes, Fernanda (2019)
Cancer is a leading cause of death worldwide, and its incidence is continually increasing. Although anticancer therapy has improved significantly, it still has limited efficacy for tumor eradication and is highly toxic to healthy cells. Thus, novel therapeutic strategies to improve chemotherapy, radiotherapy and targeted therapy are an important goal in cancer research. Macroautophagy (herein referred to as autophagy) is a conserved lysosomal degradation pathway for the intracellular recycling of macromolecules and clearance of damaged organelles and misfolded proteins to ensure cellular homeostasis. Dysfunctional autophagy contributes to many diseases, including cancer. Autophagy can suppress or promote tumors depending on the developmental stage and tumor type, and modulating autophagy for cancer treatment is an interesting therapeutic approach currently under intense investigation. Nutritional restriction is a promising protocol to modulate autophagy and enhance the efficacy of anticancer therapies while protecting normal cells. Here, the description and role of autophagy in tumorigenesis will be summarized. Moreover, the possibility of using fasting as an adjuvant therapy for cancer treatment, as well as the molecular mechanisms underlying this approach, will be presented.